EFEKTIVITAS KONSUMSI BAWANG PUTIH PANGGANG, RELAKSASI NAPAS DALAM, DAN RELAKSASI AUTOGENIK TERHADAP PENURUNAN TEKANAN DARAH PENDERITA HIPERTENSI - Susmadi, Susmadi; Sunita, Anna; Sutiarti, Eti; Ngadiarti, Iskari (Poltekkes Kemenkes Bandung, 2024)
Hypertension is a worldwide health problem that causes complications of kidney damage, coronary heart disease, stroke, disability, and even death. Roasted garlic, slow deep breathing relaxation, and autogenic relaxation are complementary alternative therapies that have not been fully utilized. These therapies are scientifically meaningful, so they need to be developed. This study aimed to determine the effectiveness of roasted garlic consumption, autogenic relaxation, deep breath relaxation on blood pressure reduction. The research design is Quasi-Experiment with control group Pre-test Post-test. Sampling method using non-probability random sampling - purposive sampling. The sample in 1 group is at least 30 respondents. Anticipating lost to follow-up of 10%, each group was 31-32 respondents. The sample was of productive age in the West Bogor. All groups were given hypertension management leaflets. Intervention group I consumed roasted garlic for 3 days at the rate of 15-17 grams morning and evening. Intervention group II performed breath relaxation morning and evening for 3 days. Intervention group III performed autogenic relaxation, while the control group was only given hypertension management leaflets. The results showed that consumption of roasted garlic compared to the control on systole p=0.001 and diastole p=0.001, autogenic relaxation compared to the control, systole p=0.042 and diastole p=0.009, deep breath relaxation compared to the control, obtained systole p=0.367 and diastole p=0.125. It is concluded that roasted garlic is more effectively used to reduce hypertensive patients' systole and diastole blood pressure. The recommendation is that roasted garlic can reduce blood pressure in hypertensive patients.